INFLUENCE OF MASS MEDIA ON SOCIAL CULTURE OF COMMUNITIES - Winda Kustiawan; H. Erwan Efendi; Kaya Arfah; Muhammad. Zul Akbar Shah (INFOKUM, 2022)
The mass media is one of the factors that play an important role in social and cultural change in society. The role of the mass media in social and cultural change in society is always related to the diffusion of innovation, where change is driven by the spread of new knowledge in society. The mass media has a role in the occurrence of social change in three aspects 1) Changes in people's mindset, 2) Changes in people's attitudes and 3) Changes in culture. The mass media is the benchmark for society to get information. By using a literature review, this paper aims to see how the role of the mass media and its contribution to all innovations that develop in society. The role of the mass media in education makes changes in the mindset and mentality of the nation. The role of the mass media in the field of information dissemination can change people's attitudes. The role of the mass media in the entertainment community produces cultural material. In carrying out all these roles, the mass media has a positive or negative impact according to people's readiness to accept something new and the mass policy of media owners to carry out their role in society